Irreverent history : essays for M.G.S. Narayanan - Narayanan, M. G. S.; Veluthat, Kesavan; Davis, Donald R. (Greenwood Press, 2014)
M.G.S. Narayanan, born 1932, historian from Kerala; contributed articles.